Análise da capacidade de hospedagem de geração fotovoltaica com inversores inteligentes e sistemas de baterias em redes de distribuição - Sousa, Jader Filipe Braga de (2019)
This work presents a proposal to evaluate the photovoltaic hosting capacity of low voltage distribution networks, by utilizing smart inverters and battery energy storage system, aiming to increase the distributed energy resources penetration. The minimum hosting capacity was determined for several scenarios in order to establish a secure margin of penetration, in which new distributed generation units can be installed independently of its network location until reaching this level. The simulations were performed to assess the hosting capacity with conventional inverters in a test feeder, using actual solar radiation data and residential demand profiles. Afterwards, it was verified the possibility of increasing the network hosting capacity using controls modes available in residential-scale smart inverters. The battery energy storage system was also evaluated and demonstrate to be effective to increase the network hosting capacity. The results of this study showed that the proposed solutions can increase the maximum penetration allowed by the feeder, bringing benefits by postponing network conventional investments such as conductors and assets replacement.